Suicidal ideation among young Afghanistan/Iraq War Veterans and civilians: Individual, social, and environmental risk factors and perception of unmet mental healthcare needs, United States, 2013. (30th November 2016) - Logan, Joseph; Bohnert, Amy; Spies, Erica; Jannausch, Mary
Abstract: Suicidal Ideation among Afghanistan/Iraq War Veterans remains a health concern. As young Veterans adjust to civilian life, new risk factors might emerge and manifest differently in this group versus those in the general population. We explored these differences. With 2013 National Survey on Drug Use and Health data, we examined differences in risk of past-year suicidal ideation between Veterans of the Afghanistan/Iraq War periods aged 18–34 years (N=328) and age-comparable civilians (N=23, 222). We compared groups based on individual and socio-environmental risk factors as well as perceptions of unmet mental healthcare needs. We report adjusted rate ratios (aRRs); interaction terms tested for between-group differences. PY suicidal ideation rates for Veterans and civilians did not differ (52 versus 59 per 1, 000, p=0.60) and both groups shared many risk factors. However, drug problems and perceived unmet mental health care needs were vastly stronger risk factors among Veterans versus civilians (interaction terms indicated that the aRRs were 3.8–8.0 times higher for Veterans versus civilians). Other differences were discovered as well. Past-year suicidal ideation rates did not differ by Veteran status among young adults. However, different risk factors per group were detected, which can inform Veteran suicide prevention efforts. Highlights: Suicidal ideation risk was compared between young Veterans and civilians. Past-year suicidal ideation rates did not differ between groups in general. Drug problems were stronger risk factors among Veterans versus civilians. Perceived unmet mental health care needs was a stronger risk factor for Veterans. Perpetration of violent assaults predicted suicidal ideation among civilians alone.